Efektivitas Diafragmatic dan Pursed Lip Breathing Exercise Terhadap Frekuensi Nafas Pasien Asma - Selvia, Selvia Novitasari; Nopia Wati; Weti (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2022)
Background, bronchial asthma is a type of long-term or chronic disease of the respiratory tract characterized by inflammation and narrowing of the airways which causes shortness of breath or difficulty breathing. Apart from having difficulty breathing, people with asthma can also experience other symptoms such as chest pain, coughing and wheezing. The purpose of this study was to determine the effectiveness of diaphragmatic and pursed lip breathing exercise on respiratory frequency in asthma patients in Public Health Center Jembatan Kecil Bengkulu City. Methods. This type of research is a quantitative study using a Quasy Experiment design with a research design of two groups pre test and post test design. Samples in the study of asthma patients were taken from January-December 2020 and January-April 2021 in Public Health Center Jembatan Kecil Bengkulu City. Results, from the results of statistical tests, it was found that the p-value before and after pursed lip breathing intervention was 0.001, which means that there was an effect on the frequency of breathing in asthmatic patients and the intervention before and after diaphragmatic breathing exercise was p value 0.002, meaning influence on the frequency of breath in asthma patients. Meanwhile, the average difference in frequency reduction in patients with asthma was the most effective diaphragmatic breathing exercise intervention with an average value of 2.750. Conclusion, the most effective intervention between pursed lip breathing and diaphragmatic breathing exercise is the diaphragmatic breathing exercise intervention.